Determinants of job satisfaction: The role of person-organisation fit, decent work and employee-organisational factors on job satisfaction - Vongai Ruzungunde; Hamfrey Sanhokwe; Willie Chinyamurindi (South African Journal of Economic and Management Sciences)
Background: The manufacturing sector is noted to be important to the South African economy. Calls exist to understand those factors that enhance the workforce capability of the manufacturing sector.